Detection of influenza virus in urban wastewater during the season 2022/2023 in Sicily, Italy - Maida, Carmelo Massimo; Mazzucco, Walter; Priano, Walter; Palermo, Roberta; Graziano, Giorgio; Costantino, Claudio; Russo, Arianna; Andolina, Gina; Restivo, Isabella; Giangreco, Viviana; Iaia, Francesca Rita; Santino, Arianna; et al. (Frontiers in Public Health, 2024)
Introduction: seasonal influenza generally represents an underestimated public health problem with significant socioeconomic implications. Monitoring and detecting influenza epidemics are important tasks that require integrated strategies. Wastewater-based epidemiology (WBE) is an emerging field that uses wastewater data to monitor the spread of disease and assess the health of a community. It can represent an integrative surveillance helpful tool for better understanding the epidemiology of influenza and prevention strategies in public health. Methods: we conducted a study that detected the presence of Influenza virus RNA using a wastewater-based approach. Samples were collected from five wastewater treatment plants in five different municipalities, serving a cumulative population of 555,673 Sicilian inhabitants in Italy. We used the RT-qPCR test to compare the combined weekly average viral loads of Influenza A and B viral RNA in wastewater samples with the average weekly incidence of Influenza-like illness (ILI) obtained from the Italian national Influenza surveillance system. We also compared the number of positive Influenza swabs with the viral RNA loads detected from wastewater. Our study investigated 189 wastewater samples. Results: cumulative ILI cases substantially overlapped with the Influenza RNA load from wastewater samples. Influenza virus viral RNA trends in wastewater samples were similar to the rise of ILI cases in the population. Therefore, wastewater surveillance confirmed the co-circulation of Influenza A and B viruses during the season 2022/2023, with a similar trend to that reported for the weekly clinically confirmed cases. Conclusion: wastewater-based epidemiology does not replace traditional epidemiological surveillance methods, such as laboratory testing of samples from infected individuals. However, it can be a valuable complement to obtaining additional information on the incidence of influenza in the population and preventing its spread.